Breeding and Lactation Efficiencies, Production Profile, Productive Herd Life and Lifetime Productivity of Gir Cows in their Home Tract - Gadariya, MR; Vataliya, PH; Murthy, KS; Ghajbi, PU (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
Breeding and lactation efficiencies (BE and LE), parity-wise production profile, productive herd life and lifetime milk production (LTMP) of Gir cows (N=309), based on 1363 calvings during 1991 to 2010 at Cattle Breeding Farm, JAU, Junagadh were studied. Age at first calving (AFC) and calving interval (CI) of Gir cows were 1527.76±14.17 and 481.22±4.86 days, respectively. CI ranged from 386 to 505 days among different lactations. When AFC and CI were taken into account together, BE of the cows as per Tomar (BE-T) was estimated to be 86.91±0.49 %. About 17 % of Gir cows in the herd calved for the first time at
Keywords: Gir cattle; Breeding efficiency; Lactation efficiency; Production profile; Herd life; Lifetime productivity